The Left Atrioventricular Coupling Index as a Predictor of Major Cardiovascular Events in Chronic Heart Failure Patients at Adam Malik Hospital Medan - Alfuadi , Rifki Mirza; Lubis , Anggia Chairuddin; Ade Putra , Yuke Sarastri-Hilfan (CoinReads Media Prima, 2025)
Introduction: Chronic heart failure (CHF) is a major global health challenge, with high prevalence and significant mortality, particularly in Indonesia, where it exceeds 5%. The left atrioventricular coupling index (LACI), a novel parameter combining left atrial (LA) and left ventricular (LV) metrics, has emerged as a potential predictor of major cardiovascular events (CVE) in CHF. This study investigates LACI’s prognostic value in predicting CVE and mortality in CHF patients. Methods: A retrospective case-control study was conducted at H. Adam Malik Hospital, Medan, from February 2025, involving 140 CHF patients meeting inclusion criteria (age ≥18 years, diagnosed with CHF due to hypertension or coronary artery disease, and underwent echocardiography). Exclusion criteria included atrial fibrillation, significant valvular disease, or prior coronary revascularization. LACI was calculated as the ratio of LA volume index (LAVI) to medial mitral annular velocity (a′). Major CVEs, including death, acute coronary syndrome, stroke, malignant arrhythmias, heart failure readmission, and revascularization, were assessed. Statistical analyses included descriptive statistics, normality tests, group comparisons (Mann-Whitney U or t-test), ROC curve analysis, and multivariate regression. Results: Of 140 patients (82.9% male, mean age 56.44±9.92 years), 28.6% experienced CVEs. LACI >6.35 was significantly associated with CVEs (P=0.0001, OR: 5.021, 95% CI: 2.289–11.014), with an AUC of 0.736 (95% CI: 0.642–0.829), sensitivity of 65%, and specificity of 70%. Multivariate analysis confirmed LACI as an independent predictor (P=0.000, Exp(B)=5.382, 95% CI: 2.304–12.568). Conclusion: LACI is a robust independent predictor of CVEs in CHF, supporting its role in early risk stratification and clinical management